Effects of Sodum Bicarbonate supplementation on Renal function and Nutritional status in Chronic Kidney Disease patients (Journal of Dhaka National Medical College & Hospital, 2017)
Background: Metabolic acidosis is commonly associated with chronic kidney disease which causes progressive loss of kidney function. The diminishing ability of the kidneys to maintain acid-hase homeostasis results in acid accumulation, leading to various complications such as impairment in nutritional status, worsened uremic bone disease and an association with increased mortality. Recent clinical trials have suggested that correction or prevention of metabolic acidosis by alkali administration is able to attenuate kidney damage and to slow progression of chronic kidney disease and improve nutritional status.Methods: It was a prospective study. Out of a total of 66 CKD patients (eGFR